Techno-Economic Assessment of Demand-Driven Small-Scale Green Hydrogen Production for Low Carbon Agriculture in Sweden - Janke, Leandro; McDonagh, Shane; Weinrich, Sören; Nilsson, Daniel; Hansson, Per-Anders; Nordberg, Åke (Frontiers in Energy Research, 2020)
Wind power coupled to hydrogen (H2) production is an interesting strategy to reduce power curtailment and to provide clean fuel for decarbonizing agricultural activities. However, such implementation is challenging for several reasons, including uncertainties in wind power availability, seasonalities in agricultural fuel demand, capital-intensive gas storage systems, and high specific investment costs of small-scale electrolysers. To investigate whether on-site H2 production could be a feasible alternative to conventional diesel farming, a model was built for dynamic simulations of H2 production from wind power driven by the fuel demand of a cereal farm located on the island of Gotland, Sweden. Different cases and technological scenarios were considered to assess the effects of future developments, H2 end-use, as well as production scale on the levelised- and farmers’ equivalent annual costs. In a single-farm application, H2 production costs varied between 21.20-14.82 €/kg. By sharing a power-to-H2 facility among four different farms of 300-ha each, the specific investment costs could be significantly decreased, resulting in 28% lower H2 production costs than when facilities are not shared. By including delivery vans as additional H2 consumers in each farm, costs of H2 production decreased by 35% due to the higher production scale and more distributed demand. However, in all cases and technological scenarios assessed, projected diesel price in retailers was cheaper than H2. Nevertheless, revenues from leasing the land to wind power developers could make H2 a more attractive option even in single-farm applications as early as 2020. Without such revenues, H2 is more competitive than diesel where power-to-H2 (PtH2) plants are shared by at least two farms, if technological developments predicted for 2030 come true. Also, out of 20 different cases assessed, 9 of them showed a carbon abatement cost lower than the current carbon tax in Sweden of 110 €/tCO2, which demonstrate the potential of PtH2 as an effective strategy to decarbonize agricultural systems.